Antecedents Word of Mouth Intention in the Restaurant Industry - Juliana, Juliana; Pramezwary, Amelda; Maleachi, Sandra; Goeltom, Vasco Adato H. (LPPM Institut Pendidikan Nusantara Global, 2024)
A restaurant is a place that provides good service to all its customers, both in the form of food and drinks. This research aims to investigate the antecedents word of mouth intention This research uses a quantitative approach with a survey method. with a sample size of 102 respondents. The data collection tool in this study used an online questionnaire which was distributed to respondents using a non-probability sampling approach using a purposive sampling technique with the criteria of using respondents who visited the restaurant at least once a year. Data analysis using PLS-SEM. The contribution of this research is to expand the factors that influence positive customer feelings towards restaurants such as environmental quality, food quality, service quality, and comfort. Service Encounter and Awareness as mediation to explain its influence on word-of-mouth intention. The results show that food quality, personal interaction quality, physical environment quality, perceived value, Service Encounter, and Awareness have a significant effect on word-of-mouth intention. This research implies that there is an influence between food quality, personal interaction quality, physical environment quality, and perceived value with word-of-mouth intention, so it can be concluded that food quality and interaction quality can shape customer relationships in providing positive recommendations about restaurants so that customers will visit. return to the restaurant.